Volume Tables of Alnus nepalensis - Mittal, M. C.; Singh, Jai; Rawat, J. K. (Indian Forester, 1990)
In tbe present paper Volume Table for Alnus nepalensls bas been prepared on the standard method or regression but special emphasis bas been put to a great extent to overcome the difficulties in finding out the best fit volume equation. For this an Index known as Fernival Index has been used for comparing the statistics or transformed and nontransformed equations.